The Effect of High Intensity Interval Training (HIIT) on Reaction Time Study Among Medical Student in Semarang - Chikita Dian Rahma Saphira; Sumardi Widodo; Arinta Puspita Wati; Tanjung Ayu Sumekar (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Reaction time is a cognitive-motoric connection that is important in making quick decisions. Due to the lack of time, medical student has low physical activity.  High Intensity Interval Training (HIIT) is a strong and intense exercise interspersed with low intensity exercise that does not require much time. It has been known that can improve cognitive function.Objective: To determine the effect of HIIT on an individual’s reaction time.Methods: Quasi-experimental research with pre-test and post-test groups design. The research subjects were 29 medical students of Diponegoro University, woman, normal IMT, 18-22 ages, has no neurologic deficit. The control group instructed not to do any physical exercises (n=15) and the experimental group was given an intervention of HIIT exercises that consists of warm-up, core, and cool-down movements for 6 weeks (n=14). Reaction time scores before and after were measured using the Attention Network Test (ANT). The significance of the data was analyzed using the paired sample t-test the independent sample t-test.Results: A significant decrease in reaction time scores (p=0,007) in both the experimental and control groups. A significant difference in reaction time scores (p=0.007) between the experimental group before and after the intervention was 592,07±74,82 to 517,21±56,77 milisecond. A significant difference in reaction time scores (p=0.024) between the control group before and after the intervention was 611,73±78,93 to 574,06±47,06 milisecond.Conclusion: HIIT for 6 weeks has been proved to reduce reaction time scores.  Keywords: High Intensity Interval Training, Physical Exercise, Reaction Time, Attention Network Test.